Discharge parameters of magnetoplasma compressor: effect of external axial magnetic field - Solyakov, D.G.; Volkova, Yu.Ye.; Marchenko, A.K.; Ladygina, M.S.; Staltsov, V.V.; Petrov, Yu.V.; Chebotarev, V.V.; Merenkova, T.M.; Makhlaj, V.A.; Yeliseyev, D.V. (Вопросы атомной науки и техники, 2020)
This paper reports the findings of our recent experiments on the evaluation of the external axial magnetic field effect on the discharge parameters of a magnetoplasma compressor (MPC). The discharge-voltage characteristics were obtained for varied magnitudes of an external axial magnetic field produced by a solenoid installed on the accelerating channel. Present experiments were carried out with helium (at the initial pressures of 2 and 10 Torr) and argon (at the initial pressure of 1 Torr) as working gases at different initial voltages. The external magnetic field varied up to 0.4 T. The discharge-voltage characteristics can be altered by the magnitude of the external magnetic field, as well as by the geometrical properties of an accelerating channel.